Preferred stock: Some insights into capital structure - Kallberg, Jarl; Liu, Crocker H.; Villupuram, Sriram (Journal of Corporate Finance, 2013)
This study analyzes the reactions of equity holders and bondholders to the announcement of 427 preferred stock issues. We document an average equity announcement effect of −0.65%. This reaction is positively influenced by a number of measures of firm creditworthiness and transparency and is higher for bank issuers. The equity market reaction is negatively influenced by convertibility (and the moneyness of the embedded option) and by the firm's accounting treatment of the issue (specifically if the issue is classified as equity). We find that average credit default swap spreads decrease by 50 basis points after the issue announcement. This decrease is also larger for more creditworthy and transparent firms. Convertibility and the moneyness of the embedded option further decrease the CDS spread. In aggregate, the decrease in equity value is much smaller than the increase in the value of the issuer's debt.